Directorial Vision Between The Closed And Open In The Iraqi Theater Space (Al-Academy, 2017)
This research deals with the concept of space in the theatrical performance and how the director works between two different spaces, the closed space and the open space. The question was how to use space according to the director's vision in the presentation. The problem of the research was whether the director of the Iraqi filmmaker could see the variable in the architectural space Or the place or space within the exhibition between open and closed, through the formation of the vision of the external components of intellectual and aesthetic and aesthetic, and impact on the relationship between the actor and the recipient to produce a new aesthetic space, and then the purpose of research and importance and limits and terminology The second study deals with the theoretical framework of the theoretical framework and the research procedures in which the researcher analyzed the sample of his research. My drama of darkness and a faction on the road to death by Adel Karim. The research then came out with a set of conclusions and conclusions, a list of sources and a summary in English